2021
DOI: 10.21203/rs.3.rs-636090/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants for Acceptance of COVID-19 Vaccine among Nigerians

Abstract: AimTo assess the degree and determinants of COVID-19 Vaccine among NigeriansMaterials and methodsFollowing appropriate ethical protocol, a population-based cross-sectional study conducted from November 2020 to January 2021 using a pretested, self-administered questionnaire from a previous study adapted to suit the Nigeria setting and distributed among Nigerians aged 18 years and above. The country was grouped in to three regions: East, North and West representing the major ethnic groups in Nigeria. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
0
1
Order By: Relevance
“…Furthermore, there is a statistical association between the level of the acceptance of Covid-19 vaccination and the number of years in service, marital status, designated work, and the type of medical facility. This finding is contrary to the finding of a study conducted in Nigeria, where it was reported that a significant association exist between vaccine acceptance or uptake and gender, tribe/ethnicity, religion, and place of residence [33]. On the other hand, a study revealed that increasing age, the influence of heads of the institution, trust in the government, and readiness to pay for the vaccine were associated with acceptance of the Covid-19 vaccine among health science students [25].…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, there is a statistical association between the level of the acceptance of Covid-19 vaccination and the number of years in service, marital status, designated work, and the type of medical facility. This finding is contrary to the finding of a study conducted in Nigeria, where it was reported that a significant association exist between vaccine acceptance or uptake and gender, tribe/ethnicity, religion, and place of residence [33]. On the other hand, a study revealed that increasing age, the influence of heads of the institution, trust in the government, and readiness to pay for the vaccine were associated with acceptance of the Covid-19 vaccine among health science students [25].…”
Section: Discussioncontrasting
confidence: 99%